ISSUES OF CALCULATION AND IMPROVEMENT OF INCOME TAX FROM INDIVIDUALS (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The article highlights, based on a study of the best practices of foreign countries in improving tax systems, it is necessary to develop a scientific proposal and practical recommendations on ways to improve this tax, taking into account the requirements of the present time.